Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s13046-018-0947-4
|View full text |Cite
|
Sign up to set email alerts
|

LAT2 regulates glutamine-dependent mTOR activation to promote glycolysis and chemoresistance in pancreatic cancer

Abstract: BackgroundReprogrammed energy metabolism has become an emerging hallmark of cancer in recent years. Transporters have been reported to be amino acid sensors involved in controlling mTOR recruitment and activation, which is crucial for the growth of both normal and tumor cells. L-type amino acid transporter 2 (LAT2), encoded by the SLC7A8 gene, is a Na+-independent neutral amino acid transporter and is responsible for transporting neutral amino acids, including glutamine, which can activate mTOR. Previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 26 publications
2
61
0
Order By: Relevance
“…In our previous research, we found that L-type amino acid transporter 2 (LAT2), an oncogenic protein in pancreatic cancer cells, could Gln-dependently activate mTOR to inhibit apoptosis and promote glycolysis. Both of them give rise to the gemcitabine-resistant phenotype, whereas mTOR inhibitor (RAD001) could solve such gemcitabine resistance [152]. Overexpressed Nampt provides massive NAD, sustaining enhanced glycolytic activity and contributing to gemcitabine resistance as well.…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous research, we found that L-type amino acid transporter 2 (LAT2), an oncogenic protein in pancreatic cancer cells, could Gln-dependently activate mTOR to inhibit apoptosis and promote glycolysis. Both of them give rise to the gemcitabine-resistant phenotype, whereas mTOR inhibitor (RAD001) could solve such gemcitabine resistance [152]. Overexpressed Nampt provides massive NAD, sustaining enhanced glycolytic activity and contributing to gemcitabine resistance as well.…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
“…Enhanced Gln metabolism fuels elevated HBP and glycosylation. Moreover, Gln addiction is also significant for controlling ROS generation and activating mTOR, both of which contribute to chemoresistance [152,156]. ROS production in pancreatic cancer cells triggered by gemcitabine treatment is presumed to be related to the dose.…”
Section: Chemoresistance and Metabolismmentioning
confidence: 99%
“…The transporters capable of importing glutamine such as ATB 0,+ ( SLC6A14 gene), SNAT1 ( SLC38A1 gene), ASCT2 ( SLC1A5 gene), LAT1 ( SLC7A5 gene), and LAT2 ( SLC7A8 gene) [ 42 ] are crucial in cancer metabolic remodeling often being upregulated in tumors [ 43 , 44 , 45 , 46 , 47 ]. Therefore, glutamine transport targeting is currently being addressed in pre-clinical trials.…”
Section: Glutamine-glutamate Relevance In Cancermentioning
confidence: 99%
“…Therefore, further studies in this area are required and could have the potential to contribute to the field of cancer research, and more particularly lung cancer. SLC7A8 or LAT-2 is an L-type amino acid transporter-2 protein that binds and regulates mechanistic target of rapamycin kinase (mTOR) activation in pancreatic cancer [69]. L-type amino acid transporters are known to be novel targets for cancer therapy [70,71].…”
Section: Discussionmentioning
confidence: 99%